Erectile Dysfunction in the Elderly: An Old Widespread Issue with Novel Treatment Perspectives. (17th March 2014) - Gareri, Pietro; Castagna, Alberto; Francomano, Davide; Cerminara, Gregorio; De Fazio, Pasquale
Abstract : Erectile dysfunction (ED) is one of the most common chronic diseases affecting men and its prevalence increases with aging. It is also the most frequently diagnosed sexual dysfunction in the older male population. A number of different diseases potentially worsening sexual function may occur in elderly people, together with polypharmacy. Related causes of ED are variable and can include arterial, neurogenic, hormonal, cavernosal, iatrogenic, and psychogenic causes. The aim of the present review was to examine the main aspects of erectile dysfunction going through epidemiology and pathophysiology and revise most of ED in elderly disabled men and in those affected with psychiatric disorders. Lastly we tried to focus on the main aspects of nonpharmacological and pharmacological treatments of ED and the recreational use in the elderly. Phosphodiesterase-5 inhibitors (PDE5-I) are commonly used for on-demand or chronic treatment of ED. It is widely known that PDE5-I have lower response rates in older men than in younger patients, but they have the advantages of ease of use and excellent safety profile, also in the elderly. The old and new PDE5-I as well as the alternative treatments for ED are extensively discussed.